Bibliometric Analysis of Socio-Economic Progress Research: A Case Study of ESAF Bank Customers - Cherian, Aiswarya; T.T., Arunkumar (NPRC Journal of Multidisciplinary Research, 2024)
This study conducts a bibliometric analysis to examine research on socio-economic progress, focusing on ESAF Bank customers. By analyzing publications, citation patterns, and key trends, the study identifies the most influential research, prevalent themes, and gaps within the literature. The findings provide insights into the role of microfinance in socio-economic development, particularly through ESAF Bank’s interventions. This analysis not only highlights the academic landscape surrounding socio-economic progress but also serves as a valuable reference for future research, policymakers, and stakeholders aiming to enhance microfinance’s impact on community development